Microwave-assisted LDHs organic functionalization method based on steel slag
Through the microwave-assisted LDHs organic functionalization method based on steel slag, ultrasonic, microwave, magnetic field and laser technology, the problems of high cost, low efficiency and insufficient performance in LDHs preparation are solved, and efficient and low-cost LDHs preparation is achieved, which meets the needs of the Performance requirements for high-end applications.
Patent Information
- Application Number
- CN202411658324.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-17
AI Technical Summary
The existing LDHs preparation technology has problems of high cost, low efficiency and insufficient performance, especially in high-end applications, which is difficult to meet the needs of environmental protection and energy storage.
The organic functionalization method of microwave-assisted LDHs based on steel slag is adopted to improve the performance and application potential of LDHs through ultrasonic pretreatment, microwave heating, magnetic field-assisted arrangement, temperature-controlled phase change and laser fine regulation.
It significantly reduces production costs, improves production efficiency, reduces energy consumption, enhances the controllability and performance of materials, and meets the needs of high-end applications such as environmental governance and energy storage.
Smart Images

Figure CN119318939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of multi-layered double hydroxides, in particular to a microwave-assisted organic functionalization method of LDHs based on steel slag. Background Art
[0002] The research on LDHs began in the 1970s. With the rapid development of nanotechnology and materials science, the synthesis methods and application scope of LDHs have been significantly expanded. Traditional synthesis methods mainly include coprecipitation, hydrothermal and sol-gel methods. In recent years, with the improvement of environmental protection and sustainable resource utilization awareness, the recycling of heavy metals from industrial waste to prepare LDHs has become a research hotspot.
[0003] The main trend of technological development is to improve the preparation efficiency and material properties of LDHs while reducing production costs. Especially in the fields of environmental protection and energy storage, the performance requirements for LDHs materials are getting higher and higher. For example, in heavy metal adsorption and wastewater treatment, the high efficiency and selective adsorption capacity of LDHs are particularly valued. In the field of energy storage, such as electrode materials for lithium-ion batteries and supercapacitors, there are extremely high requirements for the electrochemical properties and cycle stability of LDHs.
[0004] Although LDHs have demonstrated a wide range of application potential, current preparation technologies still face several challenges. First, from a cost-effectiveness perspective, traditional synthesis methods such as co-precipitation often require strict control of pH and reaction temperature, which is cumbersome and energy-intensive. Second, how to effectively extract useful components from industrial waste to prepare high-quality LDHs remains a technical difficulty. In addition, current LDHs products exhibit insufficient performance in certain applications, such as insufficient structural stability under high loads, which limits their promotion in high-end applications.
[0005] With the improvement of global environmental standards and the increase in energy demand, the market demand for high-performance, low-cost and environmentally friendly LDHs continues to grow. In particular, in the treatment of heavy metal pollution and other industrial wastes, more effective LDHs materials need to be developed to meet strict environmental emission standards. At the same time, the increasing demand for high-stability and high-capacity electrode materials in the field of energy storage has promoted the exploration of LDHs performance improvement and new synthesis methods.
[0006] In summary, in response to the shortcomings of the existing technology and the market demand, the present invention proposes a new method for efficiently preparing LDHs from steel slag, which not only utilizes industrial waste and reduces production costs, but also significantly improves the performance of LDHs through a series of innovative steps such as ultrasonic pretreatment, microwave heating, magnetic field-assisted arrangement, temperature-controlled phase change and laser fine control, providing technical guarantee for the wide application of LDHs. Summary of the invention
[0007] The purpose of the present invention is to provide a microwave-assisted organic functionalization method for LDHs based on steel slag, which solves the problem of insufficient performance of LDHs products in certain applications in the prior art.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A microwave-assisted organic functionalization method for LDHs based on steel slag comprises the following steps:
[0010] Step 1: Ultrasonic assisted slag pretreatment;
[0011] Using ultrasonic technology to treat steel slag to promote the release of metal ions; the high-frequency vibrations of ultrasound create tiny bubbles (cavitation effect), which when collapsed in the steel slag generate extremely high temperatures and pressures, thus breaking the chemical structure in the steel slag and releasing valuable metal ions;
[0012] Step 2: Microwave-promoted chemical reaction;
[0013] The treated steel slag solution and the mixture of organic silane compounds are rapidly heated by microwave heating to promote the nucleation and organic modification of multi-layered double hydroxides (LDHs);
[0014] Step 3: Magnetic field-assisted molecular alignment;
[0015] The interlayer spacing and molecular arrangement of the newly formed LDHs can be adjusted by applying an external magnetic field. The directionality and intensity control of the magnetic field can be used to precisely manipulate the microstructure of the material and optimize its electronic and magnetic properties.
[0016] Step 4: Temperature controlled phase transformation;
[0017] The temperature in the reactor is precisely controlled to promote the transformation of LDHs from one crystal phase to another more stable crystal phase;
[0018] Step 5: Fine adjustment of laser;
[0019] Laser technology is used to fine-tune the size and morphology of LDHs particles; the high energy density and controllability of lasers make them an ideal tool for adjusting the microstructure of materials.
[0020] On the basis of the above technical solution, the present invention also provides the following optional technical solution:
[0021] In an optional solution: the calculation formula of the ultrasonic energy in step 1 is: E=0.5*m*(A*omega)^2.
[0022] In an optional scheme: the calculation of the chemical reaction rate in step 2 is described by the Arrhenius equation, which is as follows: ln(k)=(-Ea / (R*T))+ln(A).
[0023] In one optional embodiment: the key formula in step three is as follows: tau = mu*B / gamma.
[0024] In one alternative: Delta G = Delta HT*Delta S + P*Delta V.
[0025] In an optional solution, the calculation of the laser energy in step 5 can be expressed by the following formula:
[0026] E = h*c / lambda.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. Reduce production costs: Existing LDHs synthesis methods such as co-precipitation and hydrothermal methods usually rely on expensive chemical reagents and equipment, as well as high-energy consumption operating conditions. The present invention reduces the dependence on high-purity chemical reagents by extracting raw materials from industrial waste, and uses microwave heating and ultrasonic technology to improve reaction efficiency, thereby effectively reducing production costs.
[0029] 2. Improve production efficiency: Traditional methods for preparing LDHs have long reaction times and low efficiency, especially in chemical environments that require strict control. This invention significantly shortens the time required for material synthesis by integrating ultrasonic pretreatment and microwave heating technology, and rapidly promotes chemical reactions through these efficient physical processes, significantly improving production efficiency.
[0030] 3. Reduce energy consumption: Existing LDHs synthesis methods such as hydrothermal method often require long-term high-temperature heating, which consumes a lot of energy. The microwave heating technology used in the present invention can achieve rapid and uniform heating, reduce energy consumption, and further optimize energy efficiency by precisely controlling the heating time and temperature.
[0031] 4. Enhance the controllability of material properties: Existing technologies have limitations in regulating the microstructure and surface functionality of LDHs, which affects the performance of the material in specific applications. The present invention allows for fine control of the layered structure and interlayer spacing of LDHs through magnetic field-assisted molecular arrangement and temperature-controlled phase change technology. In addition, laser fine control technology enables precise shaping and size control at the microscopic level, improving the functionalization and application adaptability of the material.
[0032] Through these improvements, the present invention not only solves the key problems of the prior art, but also improves the overall performance and application potential of LDHs, meeting the stringent requirements of high-end applications such as environmental governance, energy storage and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A flowchart of the process of the present invention.
[0034] Figure 2 This is a flow chart for verifying the effect of ultrasonic pretreatment of the present invention.
[0035] Figure 3 It is a data comparison and analysis flow chart of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] like Figure 1-Figure 3 As shown, the embodiment of the present invention provides a microwave-assisted organic functionalization method of LDHs based on steel slag, comprising the following steps:
[0038] Step 1: Ultrasonic assisted slag pretreatment
[0039] In the first step, we use ultrasound technology to treat steel slag to promote the release of metal ions. The high-frequency vibration of ultrasound produces tiny bubbles (cavitation effect). When these bubbles collapse in the steel slag, they generate extremely high temperatures and pressures, which break the chemical structure in the steel slag and release valuable metal ions. This method not only improves the efficiency of recovering metals from industrial waste, but also reduces environmental pollution and contributes to sustainable development.
[0040] Step 2: Microwave-promoted chemical reactions
[0041] The second step is to use microwave heating to quickly heat the treated steel slag solution and the organic silane compound mixture to promote the nucleation and organic modification of multi-layered double hydroxides (LDHs). Microwave heating can directly act on the molecular level, causing the dipole moment inside the reactant molecules to rotate rapidly and generate heat energy, thereby achieving a fast and uniform heating effect. This heating method significantly improves the speed and efficiency of chemical reactions.
[0042] Step 3: Magnetic field-assisted molecular alignment
[0043] In this step, the interlayer spacing and molecular alignment of the newly formed LDHs are adjusted by applying an external magnetic field. By controlling the directionality and intensity of the magnetic field, the microstructure of the material can be precisely manipulated to optimize its electronic and magnetic properties. The magnetic field-assisted molecular alignment technique is particularly suitable for preparing materials with specific directionality or magnetic properties, which is very valuable in high-performance electronic and energy storage devices.
[0044] Step 4: Temperature-controlled phase inversion
[0045] The fourth step is to promote the transformation of LDHs from one crystal phase to another more stable crystal phase by precisely controlling the temperature in the reactor. Precise control of temperature can affect the lattice structure of the material, rearrange chemical bonds and adjust the interlayer spacing. This control is crucial for optimizing the thermal stability, ion exchange capacity and electrochemical performance of the material.
[0046] Step 5: Laser Fine Control
[0047] In the last step, laser technology is used to fine-tune the size and morphology of the LDHs particles. The high energy density and controllability of lasers make them an ideal tool for adjusting the microstructure of materials. Through laser processing, rapid and non-contact modification of material morphology can be achieved, further optimizing the surface properties and functions of the material, which is suitable for high-precision material engineering applications such as sensors, catalysts and biomedicine.
[0048] These five steps constitute a complete material preparation and optimization process, in which each step plays a unique and interrelated role, working together to fine-tune the structure and properties of the final material. The following is the relationship between these five steps and their interaction in the entire preparation process:
[0049] Step 1: Ultrasonic assisted slag pretreatment
[0050] This step is the starting point of the entire process, and its purpose is to increase the reactivity of the material using physical methods. Through ultrasonic treatment, the chemical bonds in the slag are broken, releasing metal ions in preparation for subsequent chemical reactions. This step ensures that the potentially valuable components in the slag are fully utilized, providing the necessary raw materials for the synthesis of LDHs.
[0051] Step 2: Microwave-promoted chemical reactions
[0052] Next, the material after the first step of treatment enters the chemical reaction stage. Here, microwave heating is used to quickly and evenly heat the mixture to promote the occurrence of chemical reactions. The use of microwaves not only improves the efficiency of the reaction, but also helps to synthesize LDHs with uniform structure by precisely controlling the reaction conditions, laying the foundation for the next step of magnetic field treatment.
[0053] Step 3: Magnetic field-assisted molecular alignment
[0054] After microwave treatment, the newly synthesized LDHs are further structurally optimized by applying an external magnetic field. The application of the magnetic field makes the layered structure in the LDHs more ordered, which is crucial for the magnetic and electronic properties of the material. This step is a bridge between chemical synthesis and physical property regulation, ensuring that the functional properties of the material meet the needs of specific applications.
[0055] Step 4: Temperature-controlled phase inversion
[0056] After adjusting the structure through the magnetic field, the temperature-controlled phase transformation further stabilizes and improves the crystal structure of LDHs. By precisely controlling the temperature, the formation of certain phases can be promoted or inhibited, which is extremely important for adjusting the thermal and chemical stability of the material. The successful execution of this step depends on the optimization of the material structure and chemical composition in the first three steps.
[0057] Step 5: Laser Fine Control
[0058] Finally, laser technology is used to fine-tune the final size and shape. This step is the final "shaping" of the material, ensuring that its size and surface properties are exactly what the final application requires. The precision of laser processing also ensures the consistency of material properties from a mass production perspective.
[0059] These five steps are interdependent, and each step provides the conditions and foundation for the successful implementation of the next step. From physical treatment to chemical reaction, and then to the subsequent physical property regulation, each step is to ultimately obtain LDHs materials with excellent performance. Through this multi-step, interdisciplinary approach, the performance of the material can be precisely controlled at the microscale, achieving its high efficiency and high stability in various high-end applications.
[0060] The detailed technical principles of each step are explained as follows:
[0061] Step 1: Ultrasonic assisted slag pretreatment
[0062] Ultrasonic technology is widely used in industry in material processing and extraction processes, especially in slag treatment. Its role is to change the material structure through the medium effect of mechanical vibration and sound waves, increase the reaction surface area, and thus improve efficiency. In the slag pretreatment process, the use of ultrasound can effectively decompose the complex structure in the slag and release more valuable metal ions such as iron, magnesium, calcium, etc. This method not only improves the recovery rate of resources, but also contributes to environmental protection because it helps to reduce the generation and accumulation of waste. The mechanical vibrations generated by ultrasound can break the microstructure of materials and promote physical and chemical processes. In ultrasonic-assisted slag pretreatment, the vibration energy is transmitted through liquid or other media to produce high-frequency vibrations on the particles in the solid slag. These vibrations can produce tiny bubbles (cavitation effect), and when these bubbles collapse, they will produce extremely high temperatures and pressures, which will have a destructive effect on the chemical bonds in the slag, thereby releasing metal ions.
[0063] In this process, the calculation of ultrasonic energy is crucial. The calculation formula is as follows:
[0064] E=0.5*m*(A*omega)^2
[0065] in:
[0066] E (Energy, Joule): This is the total energy transferred from the ultrasonic equipment to the steel slag. The amount of energy directly affects the effect of ultrasonic treatment. The greater the energy, the higher the metal ion release efficiency.
[0067] m (mass, kilograms): This is the mass of the processed slag. The size of the mass determines the basis of energy conversion. The larger the mass, the more energy is required.
[0068] A (amplitude, meters): This is the amplitude of ultrasonic vibration, that is, the intensity of vibration. The larger the amplitude, the stronger the impact of the sound wave on the steel slag, and the more significant the cavitation effect.
[0069] Omega (angular frequency, radians per second): This is the angular frequency of the ultrasound, representing the speed of vibration. The higher the frequency, the more vibrations per unit time, and the stronger the impact and chemical effect on the slag.
[0070] Step 2: Microwave-promoted chemical reactions
[0071] In microwave-promoted chemical reactions, we use the thermal effect of microwaves to quickly heat the treatment process to promote the progress of the chemical reaction. Microwave heating is a very effective method because it can act directly on the molecular level, so that the dipole moment inside the reactant molecule rotates rapidly under the influence of the microwave electric field to generate heat energy, thereby achieving the effect of rapid and uniform heating. This heating method is different from traditional thermal conductive heating. It can increase the temperature of the solution in a very short time, greatly accelerate the rate of chemical reactions, and is particularly suitable for occasions where precise reaction conditions need to be controlled. In the present invention, the steel slag solution obtained after ultrasonic treatment is mixed with an organosilane compound, and then the pH value of the solution is adjusted to make it suitable for the nucleation and growth of LDHs. Subsequently, the mixed solution is quickly heated using microwave thermal energy to promote the rapid nucleation of LDHs and its organic modification.
[0072] The calculation of chemical reaction rate can be described by the Arrhenius equation, which is as follows:
[0073] ln(k)=(-Ea / (R*T))+ln(A)
[0074] in:
[0075] ln(k): The natural logarithm of the reaction rate constant, which reflects the rate of the reaction. The larger the rate constant, the faster the reaction.
[0076] Ea (activation energy, joules / mole): Activation energy refers to the energy threshold required for reactant molecules to reach sufficient energy for a chemical reaction to proceed. The lower the activation energy, the easier the reaction will proceed.
[0077] R (gas constant, joule / (mole·Kelvin)): Ideal gas constant, used in many physical and chemical calculations.
[0078] T (temperature, Kelvin): actual reaction temperature. Microwave heating causes the temperature of the reaction system to rise rapidly, which is conducive to overcoming the activation energy barrier.
[0079] A (preexponential factor, dimensionless): A constant related to collision frequency and molecular orientation, which reflects the reaction ability of the reactant molecules when they are not affected by energy.
[0080] In practical applications, this microwave-promoted chemical reaction technology can be widely used in fields such as materials science, drug synthesis and environmental engineering. For example, in environmental engineering, by rapidly synthesizing LDHs with high adsorption capacity, it can be used to treat wastewater containing heavy metals and organic pollutants. Microwave technology is particularly suitable for industrial-scale applications due to its high efficiency and energy-saving characteristics, which can significantly reduce energy consumption and improve production efficiency. In general, microwave-promoted chemical reactions can not only increase the reaction rate, but also improve the quality and performance of the products. It is an important technical approach in modern chemical manufacturing and materials science. By precisely controlling the power and reaction time of microwaves, the reaction process can be finely regulated, thereby optimizing the performance and yield of the product.
[0081] Step 3: Magnetic field-assisted molecular alignment
[0082] In materials science, magnetic field-assisted technology is an innovative method for improving and controlling the microstructure of materials, especially those with layered or molecular order, such as multi-layered double hydroxides (LDHs). By introducing a magnetic field during the material synthesis process, the microstructure of the material can be effectively manipulated to optimize the physical and chemical properties of the material. This method is particularly suitable for preparing nanostructures with specific directionality or symmetry because the directionality and intensity of the magnetic field can be precisely controlled. Magnetic field-assisted molecular alignment mainly relies on the force of the magnetic field on charged particles or molecules with magnetism, which can guide the molecules to align in a specific direction, thereby forming an ordered microstructure. In the synthesis of LDHs, the interlayer spacing and the arrangement of particles within the layer can be adjusted by controlling the magnetic field, improving the interlayer charge distribution and macroscopic properties of the material.
[0083] The key formula used in this process is as follows:
[0084] tau=mu*B / gamma
[0085] in:
[0086] tau (relaxation time, seconds): This is the time required for the magnetization vector to align with the external magnetic field. The relaxation time is an important parameter for evaluating how quickly a material responds to a magnetic field. The shorter the time, the faster the material responds to the magnetic field, indicating that the material is more likely to adjust its structure under the action of a magnetic field.
[0087] mu (magnetic susceptibility, dimensionless): This is a physical quantity that describes the degree to which a material responds to a magnetic field. Materials with high magnetic susceptibility are more easily affected by magnetic fields, and their internal structures adjust more quickly and thoroughly under the action of magnetic fields.
[0088] B (Magnetic Field Strength, Tesla): This is the strength of the applied external magnetic field. The magnitude of the magnetic field strength directly affects the efficiency and effectiveness of the material structure adjustment.
[0089] Gamma (gyromagnetic ratio, radians / (Tesla-second)): This is a physical quantity that characterizes the speed at which a material responds to rotation in a magnetic field. The larger the gyromagnetic ratio, the faster the material adjusts under the action of a magnetic field.
[0090] In practical applications, magnetic field-assisted molecular arrangement technology shows great potential in the preparation of high-performance electronic materials, magnetic materials and specific catalysts. For example, in the development of high-efficiency batteries and supercapacitors, the charge storage performance can be optimized by controlling the interlayer structure of LDHs through magnetic fields. In addition, this technology can also be applied to drug delivery systems, and the structure of drug carriers can be controlled by magnetic fields to achieve more precise drug release. In addition, magnetic field-assisted technology also plays a role in environmental governance, such as the preparation of heavy metal adsorbents. By precisely controlling the microstructure of LDHs, its adsorption capacity and selectivity for specific heavy metal ions can be improved, thereby improving treatment efficiency and environmental friendliness. In short, magnetic field-assisted molecular arrangement is a high-tech method with broad application prospects. It can not only improve the performance of materials, but also achieve multifunctionality and optimization of specific properties by precisely controlling the microstructure of materials.
[0091] Step 4: Temperature-controlled phase inversion
[0092] In chemistry and materials science, temperature-controlled phase transformation is a technique that induces the transition of a substance from one structural phase to another more stable phase by precisely controlling the temperature. For multi-layered double hydroxides (LDHs), this control is not only related to the crystal structure of the material, but also directly affects its chemical and physical properties, such as thermal stability, electronic properties, and ion exchange capacity. During the synthesis of LDHs, precise control of temperature can help achieve the transformation from a less stable precursor structure to a more ordered and stable LDHs structure. This transformation usually involves the reorganization of the crystal lattice, the rearrangement of chemical bonds, and the adjustment of the interlayer spacing, and these changes are crucial to the final performance of the material.
[0093] The thermodynamics of temperature-controlled phase transformation can be described by the Gibbs free energy change, as follows:
[0094] Delta G=Delta HT*Delta S+P*Delta V
[0095] in:
[0096] Delta G (Gibbs free energy change, in Joules): This is a measure of the spontaneity of a reaction. If Delta G is less than zero, the reaction proceeds spontaneously under the given conditions.
[0097] Delta H (enthalpy change, in joules): This represents the change in heat in the system during the reaction. A positive value indicates an endothermic reaction, and a negative value indicates an exothermic reaction.
[0098] T (temperature, Kelvin): This is the temperature of the system when the reaction is taking place, which directly affects the effect of entropy change.
[0099] Delta S (entropy change, joules / Kelvin): This is the amount of change in disorder in a system. An increase in entropy is usually associated with a system's energy dispersion and an increase in the number of microscopic states.
[0100] P (Pressure, Pascals): This is the pressure inside the system.
[0101] Delta V (volume change, cubic meters): This is the change in volume of the system due to the reaction.
[0102] In practical applications, temperature-controlled phase transformation technology plays an important role in the preparation of advanced functional materials. For example, in the development of battery materials, LDHs materials with excellent electrochemical properties can be prepared by precisely controlling the temperature during the synthesis process. These materials exhibit excellent ionic conductivity and electrochemical activity due to their specific crystal structure and chemical composition, and are suitable for use as electrode materials for batteries. In addition, temperature-controlled phase transformation is also widely used in the preparation and modification of catalysts. By adjusting the temperature under synthesis conditions, the surface properties and distribution of active sites of the catalyst can be optimized, thereby improving its catalytic efficiency and selectivity. For example, LDHs are often used as catalysts for various organic reactions due to their tunable acidity and interlayer structure. Temperature-controlled phase transformation is not limited to laboratory-scale research, but is also very critical in industrial production. In large-scale production processes, temperature control can ensure the consistency and stability of product quality, especially in applications with extremely high material performance requirements, such as aerospace, electronic equipment, and environmental engineering. In short, temperature-controlled phase transformation is a powerful tool that enables scientists and engineers to precisely control the microstructure and properties of materials, providing broad possibilities for the development of new materials and the improvement of existing materials. By precisely controlling reaction conditions, especially temperature, materials can be designed and optimized at the molecular level to achieve their optimal performance in a variety of high-tech applications.
[0103] Step 5: Laser Fine Control
[0104] Laser fine control technology is a method of using laser beams to precisely process materials. This technology is particularly suitable for adjusting the microscopic size and morphology of materials. In the synthesis process of LDHs (multi-layered double hydroxides), laser technology can be used to precisely control the size and shape of particles, thereby optimizing their physical and chemical properties. The high energy density and controllability of lasers make them an ideal tool for rapid, localized, and non-contact modifications to material structures. Laser processing relies primarily on the precise control of its energy and the interaction between light and matter. When the laser is irradiated onto the LDHs material, its energy is absorbed by the material and converted into heat energy, causing local heating of the material. This heating can cause phase changes in the material at the microscopic level, or trigger surface reconstruction and adjustment of particle size.
[0105] The calculation of laser energy can be expressed by the following formula:
[0106] E=h*c / lambda
[0107] in:
[0108] E (Energy, Joule): This is the energy of the laser, which directly determines the effect of the laser on material processing.
[0109] h (Planck constant, joule-second): This is a basic constant in quantum mechanics that describes the relationship between energy and frequency and is the smallest unit of energy exchange in quantum events.
[0110] c (speed of light, meters per second): This is the speed at which light travels in a vacuum and is used to calculate the wavelength and frequency of lasers.
[0111] lambda (wavelength, meters): This is the wavelength of the laser, which determines the type of laser and the nature of its interaction with matter.
[0112] In practical applications, laser fine control technology is widely used in fields such as materials science, nanotechnology and biomedicine. For example, in the preparation of nanomaterials, by adjusting the parameters of the laser (such as energy, wavelength, pulse width, etc.), scientists can precisely control the size and morphology of nanoparticles, which is essential for the preparation of materials with specific optical, electronic or chemical properties. In addition, laser technology has also shown great potential in the manufacture of microfluidic chips and biosensors. Through laser direct writing technology, the surface of materials can be precisely modified at a very small scale to form complex microstructures, which can be used to precisely control fluid dynamics or improve the sensitivity of sensors. In the field of medicine, laser fine control is also used in the design and preparation of drug carriers. Through laser technology, the antidote behavior of carrier materials can be precisely controlled, thereby achieving directional release of drugs and improving treatment efficiency. In short, laser fine control technology has opened up new areas of materials science and engineering by providing a highly precise and controllable way to modify the microstructure and properties of materials. The application of this technology is not limited to basic scientific research, and its potential in industrial production and high-tech product development is also being gradually explored.
[0113] Experiment 1: Verification of the effect of ultrasonic pretreatment
[0114] Purpose: This experiment aims to verify the effect of ultrasonic pretreatment on improving the release efficiency of metal ions in steel slag. By comparing the metal ion release rates before and after ultrasonic treatment, the enhancement effect of ultrasonic pretreatment on the extraction efficiency of metal ions in steel slag is evaluated.
[0115] Detailed description of experimental methods
[0116] 1. Sample preparation:
[0117] Sample selection: Select industrially produced steel slag samples to ensure the consistency of sample sources and reduce experimental variation.
[0118] Sample grouping: Take 1 kg of steel slag sample and divide it evenly into two groups, each group is 500 grams. One group is used as the control group and the other group is used as the experimental group.
[0119] Sample pretreatment: All samples were dried and screened to ensure uniform particle size (e.g., screened to <2 mm) to reduce the impact of particle size on experimental results.
[0120] 2. Ultrasonic treatment:
[0121] Equipment setup: Use an ultrasonic device with a frequency of 40kHz for the experiment. The device needs to be preheated and calibrated to ensure that the ultrasonic energy emitted is uniform.
[0122] Treatment parameters: The experimental group samples were placed in an ultrasonic device and the ultrasonic exposure time was set to 30 minutes. The control group samples were placed in the same environment but without ultrasonic treatment.
[0123] Environmental control: Ensure that the temperature and humidity in the laboratory remain constant during the experiment to avoid external factors interfering with the experimental results.
[0124] 3. Determination of metal ion release rate:
[0125] Sample treatment: After the experiment, the two groups of samples were immersed in deionized water for 24 hours to fully release the metal ions.
[0126] Metal ion determination: Atomic absorption spectrometer (AAS) was used to determine the metal ion concentration in the solution. The concentrations of iron (Fe), magnesium (Mg) and calcium (Ca) were determined respectively.
[0127] Data recording: Record and calculate the release rate of each metal ion and perform statistical analysis.
[0128] Experimental Results
[0129] Metal ion release rate in the control group:
[0130] Fe: 2.5%
[0131] Mg: 1.8%
[0132] Ca: 2.1%
[0133] Metal ion release rate in the experimental group:
[0134] Fe: 3.7%
[0135] Mg: 2.7%
[0136] Ca: 3.1%
[0137] Results Analysis
[0138] Ultrasonic treatment significantly increases the release rate of metal ions in steel slag:
[0139] Iron (Fe): increased from 2.5% to 3.7%, an increase of 48%.
[0140] Magnesium (Mg): increased from 1.8% to 2.7%, an increase of 50%.
[0141] Calcium (Ca): increased from 2.1% to 3.1%, an increase of 48%.
[0142] These data show that ultrasonic pretreatment effectively destroys the structure in steel slag through its mechanical vibration and cavitation effect, thereby increasing the extractability of metal ions in steel slag, which is of great significance for improving the efficiency of recovering valuable metals from industrial waste. Ultrasonic pretreatment is an effective technology that can significantly improve the extraction efficiency of metal ions in steel slag. This discovery provides reliable technical support for the efficient utilization of steel slag resources and environmental protection.
[0143] The flowchart below describes the detailed steps for the verification of the effect of ultrasonic pretreatment, aiming to show the whole process from sample preparation to experimental results to verify the effect of ultrasound on improving the release efficiency of metal ions in steel slag.
[0144] step:
[0145] 1. Sample preparation: Select and prepare equal amounts of steel slag samples and divide them into a control group and an experimental group.
[0146] 2. Ultrasonic treatment: The samples in the experimental group were treated with ultrasonic waves, while those in the control group were not treated.
[0147] 3. Sample soaking: The treated samples were soaked in deionized water to release metal ions.
[0148] 4. Metal ion determination: Use atomic absorption spectrometer to determine the metal ion concentration in the solution after immersion.
[0149] 5. Data analysis: Record and analyze the metal ion release rate and compare the changes before and after treatment.
[0150] 6. Result output: Summarize and report the experimental results to verify the effect of ultrasonic pretreatment;
[0151] Experiment 2: Verification of microwave-promoted chemical reaction efficiency
[0152] Purpose: This experiment aims to verify the efficiency and quality improvement of microwave heating technology in the synthesis of multi-layered double hydroxides (LDHs) compared with traditional heating methods. The specific goal is to evaluate the effect of microwave heating on the acceleration of synthesis rate and the improvement of LDHs crystal structure and particle size uniformity.
[0153] Detailed description of experimental methods
[0154] 1. Sample preparation:
[0155] Pretreatment: Ultrasonic technology is used to pretreat the steel slag to ensure that the metal ions are fully released.
[0156] Solution preparation: Mix the treated steel slag solution with the organosilane compound in a predetermined ratio to ensure that the two materials are fully integrated.
[0157] Grouping: The mixed solution was divided into two parts, one for the microwave heating experimental group and the other for the traditional heating control group.
[0158] 2. Heating conditions:
[0159] Microwave heating group: Use a microwave reactor with a power of 500 W to heat the solution for 10 minutes. Monitor the temperature change during the process to ensure uniform heating.
[0160] Conventional heating group: Heat the solution to 80°C in a sand bath for 1 hour. Monitor the temperature to ensure consistent experimental conditions.
[0161] 3. Structure and purity analysis:
[0162] X-ray diffraction (XRD) analysis: The crystal structures of the two groups of samples were analyzed, and the position, intensity, and sharpness of the diffraction peaks were recorded.
[0163] Scanning electron microscopy (SEM) analysis: Observe and record the morphology and particle size distribution of LDHs, and compare the differences between the two heating methods.
[0164] Experimental Results
[0165] XRD analysis:
[0166] The microwave heating group exhibited clear and sharp diffraction peaks, indicating that the LDHs had higher crystal integrity and fewer defects.
[0167] The diffraction peaks in the XRD pattern of the control group are broad and the crystal structure is not complete.
[0168] SEM analysis:
[0169] The particle size of LDHs in the microwave heating group was uniform, mainly distributed around 200 nm.
[0170] The particle sizes of LDHs in the traditional heating group were uneven, ranging from 200 nm to 500 nm, and had various morphologies.
[0171] Results Analysis
[0172] Microwave-heated LDHs not only show higher integrity in crystal structure, but also have significantly improved particle size uniformity. This proves that microwave heating can provide faster and more uniform heating effects, thereby improving the synthesis quality of LDHs. Compared with traditional heating, microwave heating shortens the synthesis time by about 83%, greatly improving the synthesis efficiency. Microwave heating technology provides an efficient and better quality-controlled alternative in the synthesis of LDHs. This method not only speeds up the synthesis process, but also enhances the potential application performance of the material by improving the crystal structure and particle size uniformity. These experimental data provide strong scientific support for the application of microwave heating in materials science.
[0173] The following flowchart details the steps of the microwave-assisted chemical reaction efficiency verification experiment. The main purpose of this experiment is to compare the efficiency and material quality of microwave heating with traditional heating methods in the synthesis of LDHs.
[0174] step:
[0175] 1. Sample preparation: Mix the ultrasonically pretreated steel slag solution with the organosilane compound.
[0176] 2. Group setting: Divide the mixed solution into two groups, one group is subjected to microwave heating, and the other group is subjected to traditional heating.
[0177] 3. Microwave heating: The samples in the experimental group were heated in a microwave reactor at a power of 500 W for 10 minutes.
[0178] 4. Conventional heating: Heat the control samples to 80°C in a sand bath for 1 hour.
[0179] 5. LDHs structure analysis: X-ray diffraction (XRD) was used to analyze the crystal structures of the two groups of samples.
[0180] 6. Particle size and morphology analysis: Scanning electron microscopy (SEM) was used to observe and record the particle size and morphology of LDHs.
[0181] 7. Data comparison and analysis: Compare the results of the two heating methods to evaluate the efficiency of microwave heating and the improvement of material quality;
[0182] Working principle:
[0183] 1. Ultrasonic-assisted slag pretreatment technology: Ultrasonic technology is used to pretreat steel slag, breaking the microstructure of steel slag with high-frequency vibration and cavitation effect, thereby increasing the release rate of metal ions. This step physically changes the structure of steel slag, improving the efficiency of subsequent chemical reactions and the utilization rate of reactants. It significantly improves the efficiency of extracting metal ions from waste slag, reduces dependence on chemical reagents, and thus reduces the cost and environmental impact of the entire preparation process.
[0184] 2. Chemical reactions promoted by microwave heating: Microwave heating technology is used to quickly and evenly heat the reaction mixture to promote the nucleation and organic modification of LDHs. Microwave heating can directly act on molecules, causing their internal dipole moments to rotate and generate heat, thereby accelerating chemical reactions. This method can achieve uniform heating of reactants in a relatively short period of time, accelerate the synthesis of LDHs, improve production efficiency, and reduce energy consumption.
[0185] 3. Magnetic field-assisted molecular alignment: During the synthesis of LDHs, an external magnetic field is introduced to guide and optimize the interlayer spacing and molecular alignment of the newly formed LDHs. By adjusting the intensity and direction of the magnetic field, the microstructure of LDHs can be finely controlled. This technology can improve the physical and chemical properties of LDHs, such as magnetism, conductivity, and catalytic activity, and customize material properties for specific applications.
[0186] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A microwave-assisted organic functionalization method for LDHs based on steel slag, characterized in that: The following steps are involved: Step 1: Ultrasonic assisted slag pretreatment; Using ultrasonic technology to treat steel slag to promote the release of metal ions; the high-frequency vibrations of ultrasound create tiny bubbles that, when collapsed in the steel slag, generate extremely high temperatures and pressures, breaking down the chemical structure in the steel slag and releasing valuable metal ions; Step 2: Microwave-promoted chemical reaction; The treated steel slag solution and the mixture of organic silane compounds are rapidly heated by microwave heating to promote the nucleation and organic modification of multi-layered double hydroxides (LDHs); Step 3: Magnetic field-assisted molecular alignment; The interlayer spacing and molecular arrangement of the newly formed LDHs can be adjusted by applying an external magnetic field. The directionality and intensity control of the magnetic field can be used to precisely manipulate the microstructure of the material and optimize its electronic and magnetic properties. Step 4: Temperature controlled phase transformation; The temperature in the reactor is precisely controlled to promote the transformation of LDHs from one crystal phase to another more stable crystal phase; Step 5: Fine adjustment of laser; Laser technology is used to fine-tune the size and morphology of LDHs particles; the high energy density and controllability of lasers make them an ideal tool for adjusting the microstructure of materials.
2. The method for microwave-assisted organic functionalization of LDHs based on steel slag according to claim 1, characterized in that: The calculation formula of the ultrasonic energy in step 1 is: E=0.5*m*(A*omega)^2.
3. The method for microwave-assisted organic functionalization of LDHs based on steel slag according to claim 1, characterized in that: The calculation of the chemical reaction rate in step 2 is described by the Arrhenius equation, which is as follows: ln(k)=(-Ea / (R*T))+ln(A).
4. The method for microwave-assisted organic functionalization of LDHs based on steel slag according to claim 1, characterized in that: The key formula in step three is as follows: tau = mu*B / gamma.
5. The method for microwave-assisted organic functionalization of LDHs based on steel slag according to claim 1, characterized in that: The thermodynamics of the temperature-controlled phase transformation in step 4 can be described by the Gibbs free energy change, as follows: Delta G = Delta H - T*Delta S + P*Delta V.
6. The method for microwave-assisted organic functionalization of LDHs based on steel slag according to claim 1, characterized in that: The calculation of laser energy in step 5 can be expressed by the following formula: E = h*c / lambda.